CUT OFF GRADE NIKEL LATERIT PADA BLOK 1A PT. ANUGRAH SUKSES MINING - Denzi Y. Rohmaningrum; Juanita R. Horman (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
PT. Anugrah Sukses Mining (ASM) is a company engaged in laterite nickel mining. PT. ASM has a production target of 140,000 tons / month, with an average nickel content of 1.95%. PT. ASM operates mining based on the divisions of regions or blocks of mining. Block 1A is the first block mined by PT. ASM. Block 1A has a total area of ​​490,000 m2 and is divided into three mining areas, namely pit 1, pit 2 and pit 3. This research focuses on the pit 2 mining front where limonite and saprolite as laterite nickel zonation. This research was conducted to determine the cut off grade of the laterite nickel grade of the planned sequence. Total tonnage of laterite nickel prior to pit formation was 235,943 tons, with 86,922 tons of waste, 149,021 tons of ore, 0.58: 1 of SR, and cut off grade % Ni ≥ 1.63. The total tonnage of laterite nickel after pit formed was 231,105 tons, with 81,414 tons of waste, 149,217 tons of ore, cut off grade % Ni 1.57 and 0.54: 1 of SR.